Intestinal parasites in children from native communities of Salta, Argentina (Colombia Medica, 2024)
Introduction: Intestinal parasites (IPs) mainly affect vulnerable populations, emphasizing the need for intervention in endemic areas.Objective: To identify the species of IPs present, determine their prevalence, and assess the relationship with socio-economic characteristics and anthropometric nutritional status from a panoramic perspective.Methods: Observational, correlational, and cross-sectional study on children and adolescents (1-15 years old) in Tartagal (Salta) over one year. IP infection was determined through fecal analysis using sedimentation techniques (Teleman), Baerman's culture, and Kato Katz. Demographic and socio-economic data were collected through a standardized survey. Height, weight, brachial, and cephalic circumference were measured. T-tests were used to assess differences, and Chi-square and linear correlation coefficients were used to evaluate association and logistic regressions for risk.Results: 55.4% of children and adolescents presented IPs, with Giardia lamblia and Hymenolepis nana being the most prevalent species. 31.9% of them had excess malnutrition. Risk factors for IP presence included age, overcrowding, and walking barefoot while owning a refrigerator, animal pens, proper water storage, and belonging to the Guarani ethnicity acted as protective factors. Areas with high building vulnerability and limited access to public services were observed.Conclusions: No association was observed between anthropometric nutritional status and the presence of IPs. However, an association was evident between socio-economic conditions and the risk of IP presence.